Determinants of the intention to use online and in-store mobile payment - Dang, Minh Hang (2018)
The gap between literature and practice of mobile payment services still exists because the differences between online and physical-world payments are not comprehensively examined. To close this gap, the paper aims to study the determinants of the intention to use mobile payment for both online and in-store transactions. A conceptual model is developed from the Technology Acceptance Model (TAM), the Unified Theory of Acceptance and Use of Technology (UTAUT) and the Task-Technology Fit Model (TTF). The paper introduces a new interaction (moderator) – Device Readiness – to unveil the impact of owning a device that allows contactless payment on customers beliefs and intention to use. Data collected from smartphone-owners in Vietnam (305 valid responses) were tested with exploring factor analysis (EFA), confirmation factor analysis (CFA) and structural equation modelling (SEM)using SPSS Amos 24.0. The results indicate that individual needs construct has the strongest positive influence on mobile payment usage intention followed by perceived usefulness, perceived benefits and perceived trust. In contrast, perceived risks factor is the burden that decreases the customer intention. Besides, the paper finds that perceived ease of use is the antecedent of perceived usefulness, perceived benefits and perceived trust. Interestingly, device readiness, themoderator, helps enhance the impact of perceived benefits construct on the intention to use. The findings provide a better understanding of factors determining behavioural intention in the context of mobile payment services. Another contribution to literature is the evidence for the interaction effect of device readiness. The paper also offers businesses and policy makers deeper insights into people perceptions towards the new industry and suggest practical strategies to improve its adoption.